The Death Penalty: Pancasila, With Efforts To Eradicated Drugs - Anggun Ariena R.; Ade Oktariatas Ky (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The rise of drugs criminal in Indonesia at this time, making Indonesia would be drugs emergency. Drugs is an extraordinary crime and need special attention in the eradication effort. Therefore it takes great strength to use legal action heaviest where Indonesia has a death penalty sentence. The purpose of the death penalty is to give hard effect for drugs criminal and as  warning for the others. The reality of the death penalty in Indonesia shows the operation of the judicial system is not good and execution is always in delay so impressed indecisive. Besides setting the death penalty also raises the debate between the ethical values of Pancasila with positive law (KUHP)No doubt that in an effort to implement the firmness some time sencountered resistance from both inside and outside the country. As well as various opinion will counter the unwarranted death penalty violates human rights. In Indonesia even for the cons of the death penalty, related with violating the first principle of Pancasila, which God as ruler of the universe that has a full provision of the right to life and death of his creatures. But Indonesia still apply the death penalty is based on the rule of law  (KUHP).